Optimal Timing of Percutaneous Coronary Intervention for Nonculprit Vessel in Patients with ST-Segment Elevation Myocardial Infarction and Multivessel Disease - Kim, Inna; Kim, Min Chul; Jeong, Hae Chang; Park, Keun Ho; Sim, Doo Sun; Hong, Young Joon; Kim, Ju Han; Jeong, Myung Ho; Cho, Jeong Gwan; Park, Jong Chun; Seung, Ki-Bae; Chang, Kiyuk; et al. (Korean circulation journal, 2017)
In patients with ST-segment elevation myocardial infarction (STEMI) and multivessel disease (MVD), the optimal timing of staged percutaneous coronary intervention (PCI) remains unclear. This study was a retrospective analysis of 753 STEMI patients with MVD who were treated by multivessel PCI in the Convergent Registry of Catholic and Chonnam University for Acute myocardial infarction (MI). Patients were divided into 3 groups according to the time from initial to staged PCI: group 1 (n=316, multivessel PCI performed during the index procedure), group 2 (n=360, staged PCI within 1 week), and group 3 (n=77, staged PCI after 1 week). The endpoint was major adverse cardiac events (MACEs), including all-cause mortality, non-fatal MI, and repeat PCI during 3.4 years follow-up. The incidence of composite MACEs was higher in group 3 than in group 1 (odds ratio [OR]: 1.83, 95% confidence interval [CI]: 1.06 to 3.18, p=0.031). However, the risk of MACEs in groups 1 and 2 was comparable (OR: 1.01, 95% CI: 0.70 to 1.46, p=0.950). In multivariate logistic regression, independent predictors of 3-year MACEs were high Killip class (OR: 2.72, 95% CI: 1.38 to 5.37, p=0.004), left ventricular ejection fraction <45% (OR: 1.57, 95% CI: 1.06 to 2.32, p=0.024), and group 3 (OR: 1.83, 95% CI: 1.06 to 3.18, p=0.009). Deferred staged PCI after one week index PCI was associated with the highest MACE, as compared to both simultaneous multivessel PCI and early staged PCI <1 week.